Juridical Review of the Position of Deeds Made by Land Deed Officials Perpetrating the Crime of Money Embezzlement Payment of Land and Building Tax - Imam, Chairul (Jurnal Konstatering, 2023)
The Land Deed Making Official (PPAT) is a public official who is given the authority to make authentic deeds regarding certain legal acts regarding Land Rights or Ownership Rights over Flat Units. However, it often happens that PPAT does things outside its authority, one of which is as the party that receives custody of PBB payments. This research aims to determine the juridical implications and responsibilities of PPAT in terms of receiving custody of Land and Building Tax (PBB) payments, then link it with appropriate theories in order to draw conclusions. The method used in the research, namely the approach method in this writing, is normative juridical, the specification of this research is analytical descriptive research. The data source uses secondary data. Data collection techniques use library research or document study. The data analysis technique uses a qualitative descriptive approach. In terms of paying PBB fees, it is basically paid by PPAT clients, but in practice it is often found that PPAT is trusted by many clients to pay their clients' PBB. In this regard, the statutory regulations do not regulate the authority of a PPAT who makes land deeds to pay land sale and purchase taxes from their clients, but if the clients give authority to the PPAT concerned to represent them to pay land sale and purchase taxes in the form of PBB to the state treasury, then the PPAT concerned basically does not have the authority to carry out such payments. This resulted in evasion of PBB tax payments to PPAT. For PPAT who commits this abuse of power, then as a result of these actions PPAT must be able to carry out accountability and be subject to appropriate criminal sanctions by the panel of judges, namely Article 372 and/or 374 of the Criminal Code and/or Articles 4,5,6 of the Republic of Indonesia Law No.8 of 2010 concerning the Crime of Money Laundering and Article 55 paragraph 1 of the Criminal Code. Keywords: Accountability; Authority; Tax.